Surface modification of PCL-gelatin-chitosan electrospun scaffold by nano-hydroxyapatite for bone tissue engineering. (March 2023) - Gautam, Sneh; Purohit, Shiv Dutt; Singh, Hemant; Dinda, Amit Kumar; Potdar, Pravin D.; Sharma, Chhavi; Chou, Chia-Fu; Mishra, Narayan Chandra
Abstract: Bone tissue engineering (BTE) has attained enough attention towards fabricating a scaffold for the treatment of bone injury. To develop an ideal scaffold, various techniques and polymers have been explored. Electrospinning has been much focused on fabricating a scaffold by taking various polymers for bone tissue engineering in recent years. In this study, a tri-polymer (PCL-gelatin-chitosan; PCL-GT-CS) scaffold was first fabricated through electrospinning. Then, the surface of the fabricated scaffold was treated with 1 wt% of nanohydroxyapatite (nHAp) for 10, 20 and 30 min. After treatment, nHAp modified PCL-GT-CS electrospun scaffold was studied by field emission scanning electron microscopy (FE-SEM) to investigate the surface morphology, fiber diameter and pore size. FE-SEM analysis revealed a uniform distribution of nHAp particles on the surface of fibers in the PCL-GT-CS scaffold after 20 min. The fiber diameter and pore size of nHAp treated scaffold (20 min) were determined and found to be 680 ± 184 nm and 5.3 ± 2.1 µm respectively. Further, X-ray diffraction (XRD), Energy dispersive X-ray spectroscopy (EDS), Fourier transform infrared (FT-IR) spectroscopy, thermogravimetric (TG) and derivative thermogravimetric analysis (DTG) suggested the presence of nHAp over the surface of PCL-GT-CS electrospun scaffold. The cell viability of human osteoblasts over the nHAp modified PCL-GT-CS scaffold was analyzed by MTT assay which was found higher than the unmodified (PCL-GT-CS) scaffold. Furthermore, DNA quantification was performed to examine the proliferation of osteoblasts which was also found significantly higher on nHAp modified scaffold than on the unmodified scaffold. Moreover, FE-SEM analysis of the scaffold, seeded with cells, depicted effective cell attachment of osteoblasts, and well-spread morphology with their characteristic polygonal shape over the modified PCL-GT-CS scaffold. Thus, an in-vitro study of nHAp modified PCL-GT-CS electrospun scaffold indicated its potential for BTE. Graphical Abstract: ga1